Developing Strategic Planning Through Organizational Performance Evaluation: A Qualitative Balanced Scorecard Analysis Based on Secondary Data - Muttaqien, Zaenal; Aziza, Shomiyatul (YCMM, 2025)
Strategic planning is a critical process that enables organizations to align their goals with performance outcomes in a dynamic operational environment. This study explores how strategic planning can be developed through organizational performance evaluation using the Balanced Scorecard (BSC) framework. Employing a qualitative approach based on secondary data analysis, the research investigates the strategic relevance of four BSC perspectives—financial, customer, internal business processes, and learning and growth—by examining organizational reports, performance audits, and planning documents. Findings indicate that while the financial and internal business process perspectives are well-integrated into strategic decision-making, the learning and growth perspective remains underutilized. The results highlight the value of secondary data in extracting actionable insights and underscore the importance of a balanced approach to performance evaluation. This study contributes to the literature by demonstrating how the BSC can be applied qualitatively to support strategic development without the need for primary data collection.